1992
DOI: 10.1007/bf00184653
|View full text |Cite
|
Sign up to set email alerts
|

Lack of effect of topically applied nicotine on pial arteriole diameter and blood-brain barrier integrity in the cat

Abstract: In the present study, the vasomotor effects of nicotine, its interaction with local chemical factors and norepinephrine, and its effects on the permeability of the blood-brain barrier (BBB) were investigated. Using perivascular microapplication, 10(-6) M nicotine was found not to exert a vasomotor effect by itself or to modify the vasodilating effect of an increase in perivascular H+, K+ and adenosine concentration. The constrictor effect of a decrease in H+, K+ or an increase in norepinephrine concentration i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

1994
1994
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
(25 reference statements)
0
6
0
Order By: Relevance
“…However, both acute and chronic in vivo nicotine exposure (at physiologically relevant doses) apparently lacks effect on BBB integrity. Specifically, acute exposure of relevant nicotine doses had little effect on tight junction integrity (Schilling et al . 1992; Chen et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, both acute and chronic in vivo nicotine exposure (at physiologically relevant doses) apparently lacks effect on BBB integrity. Specifically, acute exposure of relevant nicotine doses had little effect on tight junction integrity (Schilling et al . 1992; Chen et al .…”
Section: Discussionmentioning
confidence: 99%
“…However, both acute and chronic in vivo nicotine exposure (at physiologically relevant doses) apparently lacks effect on BBB integrity. Specifically, acute exposure of relevant nicotine doses had little effect on tight junction integrity (Schilling et al 1992;Chen et al 1995). Similar doses in chronic exposure (> 7 but £ 21 days) did not alter extravasation of macromolecules in human pulmonary epithelium (Minty et al 1984), canine femoral endothelium (Allen et al 1988), hamster cheek pouch microvessels (Myers et al 1988;Mayhan and Sharpe 1998) or rabbit aortic endothelium (although increased microvilli formation and localized areas of 'ruffled' endothelium were noted morphologically) (Booyse et al 1981).…”
Section: Discussionmentioning
confidence: 99%
“…This BBB disruption occurred as early as 2 h after acute nicotine and after 6 weeks of chronic exposure (Lin et al, 1992; Uzum et al, 1999; Venisnik, 2000;Hawkins et al, 2004, 2005). In vitro studies using either brain microvascular endothelial cells alone or in combination with C6 astrocytes revealed increases of FITC-Dextran and [ 14 C]sucrose leakage across the cells after nicotine treatment (Schilling et al, 1992; Abbruscato et al, 2002). Nicotine also decreases transendothelial electrical resistance in an in vitro BBB model (Hutamekalin et al, 2008; Rodriguez-Gaztelumendi et al, 2011).…”
Section: Stimulant Drugs and The Bbbmentioning
confidence: 99%
“… 1 Rodriguez-Gaztelumendi et al (2011); 2 Hutamekalin et al (2008); 3 Schilling et al (1992); 4 Abbruscato et al (2002); 5 Chen et al (2002); 6 Albaugh et al (2004); 7 Speer et al (2002); 8 Manda et al (2010a,b); 9 Liou et al (2007); 10 Yang et al (2006); 11 Paulson et al (2006); 12 Abbruscato et al (2004); 13 Hawkins et al (2005); 14 Uzum et al (1999); 15 Lin et al (1992); 16 Wang et al (1997); 17 Paulson et al (2010); 18 Bradford et al (2011); 19 Canis et al (2009); 20 Lockman et al (2005); 21 Wang et al (1994); 22 Gerzanich et al (2003); 23 Yong et al (1997) .…”
Section: Stimulant Drugs and The Bbbmentioning
confidence: 99%
“…This is probably due to the fact that different aspects of junctional permeability are regulated by distinct mechanisms. Furthermore, an in vivo study has shown that only toxic concentrations of nicotine (10 À4 e 10 À3 M) were able to increase the permeability to 70 kDa FITC-dextran (Schilling et al, 1992).…”
Section: Discussionmentioning
confidence: 99%